Adaptabilidad en la Gestión de Organizaciones - Una propuesta de intervención - Silva, Carlos dias da (2018)
Today companies change with the constant fluctuations of supply and demand, turbulent markets and evolving consumption habits. These realities force them to rethink their management systems and their ways of doing things: being able to adapt to change is unavoidable if you want to survive. This is why change is not just a matter of organization, technology or management; fundamentally it is a matter of culture and behaviour. Therefore the question is: What means of persuasion can we use on the personnel and culture of an organization to act as a spur to developing a greater capacity for change, learning and adaptability? Using semi-structured interviews with people impacted by organizational changes, focus groups were set up during which were identified the recurrent themes when accepting and adapting to change has taken place, ending positive results for both parties: the company and its personnel. The results show that in successful change processes concerning personnel, there are aspects which can easily be controlled by the organization, such as the knowledge and skills required for the new situation. However, there are other factors deemed to be more deep-seated, insofar as they concern beliefs and values which may be family-based and reaffirmed in the workplace. Finally, procedures are established in order to spread adaptability throughout Human Resources processes and to develop it as an essential element in the culture of a modern day organization.